Malaysian energy demand and emissions from the transportation sector - Al-Mofleh, Anwar; Taib, Soib; Salah, Wael A. (Transport, 2010)
Road transport represents one of the greatest areas of challenge for energy efficiency. A growing percentage of petrol usage is due to consumption in the transportation sector. However, in other sectors, petrol has been recently partially or totally substituted by other fuels. The need for worldwide action to achieve energy efficiency in the transportation sector has been recognized by the agencies of the United Nations and other international governmental and non‐governmental organizations. Transportation is one of the key factors for the growth and development of Malaysian economy. Currently, more than 80% of primary energy consumption based on fossil fuels and demand stays high and is supposed continually grow in the future. Even if technology developments eventually able to reduce specific consumption, world energy demand is likely to increase in line with its population. This sector also accounts for a substantial amount of air pollution in cities and contributes significantly to greenhouse gas emissions. This paper aims to analyze factors influencing the pattern and emission level of energy consumption in the transportation sector of Malaysia and extrapolates the total energy demand and vehicular emissions.First published online: 10 Feb 2011